The effect of social networking sites use on employees' knowledge sharing. Issue 2 (12th August 2020) - Vyas, Pallavi Ghanshyala; Pandey, Satish
Abstract : Purpose: The purpose of this study is to investigate the relationship of social networking sites (SNSs) use, bridging social capital (BSC) and job satisfaction (JS) with knowledge sharing (KS) of employees. With the advent of social media and its technologies, it becomes opportune for organizations and practitioners to understand if the technology has usefulness for its employees. Design/methodology/approach: After a thorough literature review, a research model was proposed and tested to identify the possible relationship between the variables. The results were validated using appropriate research tools such as hierarchical regression. Findings: SNS use, BSC and JS were found to be positively associated with KS and the three variables together influenced KS more favorably. However, there was no significant association of SNS use with JS and BSC of employees, unlike past research conducted in the context of different countries. Research limitations/implications: The authors identified the workplace implications of SNSs use in enabling KS and also the positive impact of losing network ties and JS of employees in enhancing KS. Practical implications: These findings can provide insight to managers on the importance of SNSs and the formation of lose – tie networks for aiding in KS. Originality/value: The study is the first to explore the BSC dimension in the context of SNS use and KS and propose a model to identify the association between SNS use, JS, BSC and KS in a single study.